Faktor Determinan Penerimaan Pajak Pertambahan Nilai (PPN) pada KPP Pratama Medan Kota - Muhammad Irsan; Lufriansyah Lufriansyah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine the effect of the Selft Assessment System, Tax Examination, and Tax Collection Against Value Added Tax Receipts at Medan Kota KPP. This research approach uses an associative research approach. The data collection method is done by documentation of data sourced from the Medan City KPP report. Based on sample collection conducted by using the time series data deflection index calculation, the number of research samples was obtained as many as 36 months of research samples during the 2016-2018 period. Data analysis techniques in this research are descriptive statistics, classic assumption tests which include normality test, multicollinearity test, and heteroskedacity test, multiple linear regression analysis, hypothesis testing which includes t test, f test and coefficient of determination. The results showed that the self assessment system, tax audits, and tax collection have no effect on value added tax (VAT) receipts at KPP Pratama Medan City in 2016-2018.